Implementasi Primary Checklist Care Round (PCR) sebagai Inovasi Monitoring Keperawatan pada Pasien Gastroenteritis Akut dengan Hipokalemia - Shinta Dwi Asih Shinta; Cicilia Ika Wulandari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Patients with acute gastroenteritis (GAE) accompanied by hypokalemia require continuous nursing monitoring due to the risk of fluid and electrolyte imbalances that can worsen their clinical condition. Although the use of checklists in nursing rounds has been widely reported, the application of the Primary Care Round Checklist (PCR) as a guide for systematic reassessment in GEA patients with hypokalemia is still rarely reported. This case report aims to describe the implementation of PCR in two adult patients with GEA and hypokalemia who were treated in Ward 7 of X Hospital, South Tangerang in 2026. PCR was implemented by the Nurse in Charge of Care (PPJA) using a structured checklist in each nursing round that covered general condition, gastrointestinal symptoms, hydration status, intake-output balance, electrolyte levels, therapy, patient safety, and continuity of care. The results showed that PCR facilitated systematic documentation and evaluation of patient condition developments, including changes in diarrhea frequency, hydration status, fluid balance, electrolyte levels, response to therapy, and potential safety risks. The use of the checklist also supported communication between nurses in continuity of care. Both patients showed improvement in clinical condition during treatment according to the therapy provided. These findings suggest that PCR has the potential to be a supporting instrument for systematic nursing review and documentation, although research with a larger sample size is still needed.